Mexican Energy Reforms - Bassam Fattouh; Armando Zamora; Anupama Sen (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2017)
This issue of the Oxford Energy Forum is devoted to Mexico's recent energy sector reforms. The reforms were designed to open up the country's energy sector to international and local private players, inject competition, provide new partnering opportunities for PEMEX, establish new markets domestically, and potentially strengthen Mexico as a key link between the American and international markets for energy trade. However, these landmark reforms – which have significant implications for the country's overall economy and the role of Petróleos Mexicanos (PEMEX), the state oil company that hitherto dominated its energy sector – are also not entirely without wider economic implications which need to be carefully considered as the country moves forward. This issue presents a spectrum of views on energy sector reforms in a country that continues to be important to both the regional and international energy systems.
Keywords: 330